“Já não são dois, mas uma só carne” : a heteronormatividade constitutiva do discurso litúrgico matrimonial - Matos, Marcos Paulo Santa Rosa (2017)
Based on the theoretical and methodological background of Discourse Analysis of French Tradition (AD), we have analyzed the Ritual do Matrimônio (1993), a liturgical script for the nuptial liturgy translated and adapted from the typical Latin version – Ordo Celebrandi Matrimonium (1991) –, translated and adapted by the Brazil’s National Conference of Bishops (CNBB), aiming to explain the heteronormative formation of the Catholic religious discourse materialized into liturgical formulations of the nuptial ceremony. The work is divided into three stages: i) revision of the history, fundamental concepts and AD method of work – especially, by Pêcheux (1997a, 1997b, 1997c, 2012), by Pêcheux and Fuchs (1997) and Orlandi (2010a), a synthesis of research on religious discourse as “type” – particularly Orlandi's studies (1987, 1996) – and proposition of the concept of liturgical discourse as “subtype”, alongside doctrinal and pastoral; ii) study of the historical production of the matrimonial ritual and heteronormative practice in the Catholic Church, with reference to doctrinal and canonical side issues, and with emphasis on the reformulations that took place after the Vatican Second Council (1962-1965), which undertook a general process of ecclesiastical reform in order to adapt the Church to the modern world; iii) linguistic-discursive analysis of the main enunciative forms of the Ritual do Matrimônio (1993), aimed at apprehending and describing the mode of functioning of the matrimonial ritual as a device of subjection and disciplinarization that materializes the heteronormative ideology approved by the Catholic Church. The study makes possible a desuperimposed understanding not only of the relationship between Catholic matrimonial liturgy and heteronormativity, but also of the role played by the Church as mediator between the spiritual and temporal planes, which are the pillars of the symbolic structure of Christian religious discourse (DRC).